2016
DOI: 10.3390/galaxies4030012
|View full text |Cite
|
Sign up to set email alerts
|

Powers and Magnetization of Blazar Jets

Abstract: Abstract:In this work I review the observational constraints imposed on the energetics and magnetisation of quasar jets, in the context of theoretical expectations. The discussion is focused on issues regarding the jet production efficiency, matter content, and particle acceleration. I show that if the ratio of electron-positron-pairs to protons is of order 15, as is required to achieve agreement between jet powers computed using blazar spectral fits and those computed using radio-lobe calorimetry, the magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…The results manifest that the jet of blazar contains an important fraction of eletron/positron pairs, with n pairs /n p ∼ 10 (left panel in Figure 2). Our results are consistent with previous works, where they pointed out that the electron/positron pairs were important on the number density in blazar jet (Kang et al 2014;Sikora 2016;Pjanka et al 2017). The ratio 10 pairs per proton is also consistent with the upper limit for pairs to avoid the Compton rocket effect Ghisellini 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The results manifest that the jet of blazar contains an important fraction of eletron/positron pairs, with n pairs /n p ∼ 10 (left panel in Figure 2). Our results are consistent with previous works, where they pointed out that the electron/positron pairs were important on the number density in blazar jet (Kang et al 2014;Sikora 2016;Pjanka et al 2017). The ratio 10 pairs per proton is also consistent with the upper limit for pairs to avoid the Compton rocket effect Ghisellini 2012).…”
Section: Discussionsupporting
confidence: 93%
“…However, even for the strictly leptonic SED models, and even in the limit of completely cold protons, the contribution of protons to the total jet power can be dominant, provided that γe < (np/ne)(mp/me), where ne = (n e + ) + (n e − ). In the case of no pairs (np = ne), the powers of blazar jets calculated by Ghisellini et al (2014) are found to exceed by a factor ∼ 20 the jet powers estimated using the calorimetry of radio lobes (Kang et al 2014;Sikora 2016;Pjanka et al 2017;Fan et al 2018) and radio core shifts studies (Pjanka et al 2017).…”
Section: Introductionmentioning
confidence: 82%
“…Therefore, our result supports the BZ mechanism for jet launching The magnetization and radiative efficiency are usually considered to be the indicator of acceleration mechanism occurring in blazar jets. We derive the magnetization parameter σB and radiative efficiency ηr (Kang et al 2014;Sikora 2016;Fan et al 2018),…”
Section: On the Magnetization And Radiative Efficiencymentioning
confidence: 99%